1983
DOI: 10.1161/01.hyp.5.4_pt_2.ii57
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and blood pressure regulation in normal and hypertensive subjects.

Abstract: To elucidate the mechanisms involved in calcium-mediated blood pressure (BP) control, plasma norepinephrine (NE), epinephrine, renin activity, and angiotensin II (AII) levels and the cardiovascular pressor responsiveness to NE and AII were assessed before and during acute mild hypercalcemia or short-term calcium (Ca) inhibition with nifedipine in 20 normal and five borderline hypertensive subjects. In normal subjects, systolic BP and plasma NE and epinephrine concentrations were increased significantly (p less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…Three hours after the second dose this inhibition was more marked (-98%) and it was associated with a slight but significant fall in diastolic BP, recorded by an 500 - automatic device, without tachycardia, and a further increase in active and inactive renins. Intravenous nicardipine administration induced a significant fall in BP with and without inhibition of converting-enzyme activity (Figure 2), suggesting that calcium antagonist vasodilation in healthy normotensive men is not influenced by the plasma level of angiotensin II as it has been suggested in normotensive and hypertensive patients during exogenous angiotensin II and noradrenaline infusions (Bianchetti et al, 1983;Simon & Snyder, 1984).…”
Section: Discussionmentioning
confidence: 69%
“…Three hours after the second dose this inhibition was more marked (-98%) and it was associated with a slight but significant fall in diastolic BP, recorded by an 500 - automatic device, without tachycardia, and a further increase in active and inactive renins. Intravenous nicardipine administration induced a significant fall in BP with and without inhibition of converting-enzyme activity (Figure 2), suggesting that calcium antagonist vasodilation in healthy normotensive men is not influenced by the plasma level of angiotensin II as it has been suggested in normotensive and hypertensive patients during exogenous angiotensin II and noradrenaline infusions (Bianchetti et al, 1983;Simon & Snyder, 1984).…”
Section: Discussionmentioning
confidence: 69%
“…10 In addition, the regional circulation in different areas, such as limb 8 and forearm, 9 appears to be more sensitive in hypertensive than in normotensive subjects to the arteriolar dilation induced by verapamil. Since this phenomenon has not been observed with nonspecific vasodilators such as nitroprusside, 9 it has been speculated that calcium entry blockade may disclose a primary defect in the calcium-dependent control of vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…8 - 10 In addition, diuresis and natriuresis are typically associated with the renal vasodilation induced by these drugs when administered to hypertensive subjects. 11 Furthermore, recent studies have shown that the renal vasculature of normotensive relatives of hypertensive patients is abnormally sensitive to the dilating effect of intrarenally infused diltiazem.…”
Section: Prehypertensive Renal Response To Nifedipine/mon/anari Et Almentioning
confidence: 99%
“…One of the 189 (91-550) unique features of the increased vascular sensitivity characteristic of the hypertensive state is that it is not the same for all 8.4 (3-32)* stimuli (31). Thus, the increased cardiovascular responsiveness 13.3 to NA in essential hypertension can be normalized by potassium supplementation or calcium reentry blockade in contrast 16.0 (91-2)t to that to All (3,32). The pathophysiological mechanism un-20.8 (l2-58) § derlying that difference, however, remains to be elucidated.…”
Section: Discussionmentioning
confidence: 98%